Pengaruh Kelas Pendalaman Iman Anak Lebak Arum (Piala) Terhadap Pertumbuhan Rohani Anak Usia 11-14 Tahun Di Kompleks Perumahan Lebak Arum Surabaya - Juanda Juanda (Jurnal Teologi dan Pelayanan Kerusso, 2016)
This research is titled: The Influence of class the deepening of faith in the child Lebak Arum against the spiritual growth of children aged 11-14 years in the residential complex Lebak Arum Surabaya. The purpose of this study is: First, to determine whether the class of deepening faith child in Lebak Arum has a role in any of the activities carried out; Second, to determine whether there is a change in the spirituality of children aged 11-14 years in the classroom deepening faith child in Lebak Arum. In conclusion deepening faith child class in Lebak Arum has an influence on the spiritual growth of children by 48.3 %.